Corrigendum - Turskis, Zenonas; Lazauskas, Marius; Zavadskas, Edmundas Kazimieras (Journal of Environmental Engineering and Landscape Management, 2015)
"Corrigendum." Journal of Environmental Engineering and Landscape Management, 22(7), p. |